Knowledge and awareness on novel coronavirus spread among dental fraternities in Visakhapatnam, India: A questionnaire-based survey - Ravi, Ravi Chandra (J Educ Health Promot, 2020)
INTRODUCTION: The pandemic caused by novel coronavirus (severe acute respiratory syndrome coronavirus 2) in Wuhan, China, in December 2019 is a highly contagious disease. The World Health Organization has declared the outbreak of coronavirus diseases (COVID-19) as a global public health emergency. Currently, the research on novel coronavirus is still in the primary stage. The aim of this study is to assess the knowledge and awareness on COVID-19 disease and related infection control measures among the dental fraternity in Visakhapatnam – the smart city. METHODS: A total of 808 dentists from the Visakhapatnam region completed a questionnaire-based survey on the knowledge, awareness, and infection control measures related to COVID-19 infection. The questionnaire was tailored from the guidance and information for health-care workers issued by the US Centers for Disease Control and Prevention. Suitable sampling method was used for the collection of data and the distribution of responses was presented as percentages. Explanatory statistics were performed for all groups and subgroups based on the percentage of correct responses. Individual pair-wise comparisons were done using the Chi-square test for the percentage of correct responses. RESULTS: A total of 825 participated in the survey, of which 808 dentists completely answered the survey, and the response rate was 98%. Among the respondents, males and females are 46.8% and 53.2%, respectively. There was a statistically significant difference for all the questions solicited, among age groups (P = 0.001, 0.001) and occupation (P = 0.001, 0.001, 0.004). Private practitioners seem to more awareness compared to teaching faculty, undergraduates, and postgraduates, as they have answered correctly (>70%) for almost all the questions. CONCLUSION: The inputs from the survey help us throw some light and fill up lacunae where required. There is a strong need to implement periodic educational interventions and training programs on infection control practices for COVID-19 among dentists in particular. The information from this survey helps us to make necessary changes in implementing periodic educational webinars and stress on areas where necessary, which is important for the dental fraternity for protecting themselves and shielding our society from COVID-19.